1995
DOI: 10.1109/61.368399
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory investigation of a digital protection technique for parallel transmission lines

Abstract: A k t r r t A digital algorithm for the protection of parallel "fuloo linea bar beea implemented on a 16-bit dngle board co(~pp1c1: It haa been tested on a physical model codsting of two rpchtoMwu " i connected through a double circuit lirre. Tbe algorithm is baaed on comparing magnitudes of amcats of two prnllel linea Details of the experimental set-up rab tbe d t s of oa-line tests for various oparriag conditions arc prerented A procedure to adjua tbe relay setting8 adapcively is d m iacorpontsd The resulk? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The relay will operate when the current division io the two circuits Varies by a given tolerance. Recently, this form of transverse Merential protection relaying was presented digitally in [6,7]. The protection algorithm is based on the comparison of the average current in corresponding phases.…”
Section: Intrqductiqnmentioning
confidence: 99%
See 1 more Smart Citation
“…The relay will operate when the current division io the two circuits Varies by a given tolerance. Recently, this form of transverse Merential protection relaying was presented digitally in [6,7]. The protection algorithm is based on the comparison of the average current in corresponding phases.…”
Section: Intrqductiqnmentioning
confidence: 99%
“…The previous discussion concluded that a technique based on the current magnitude only as described in [6,7] is highly influenced by the short-circuit impedance behind the buses.…”
Section: Scope On the Studied Problem Areasmentioning
confidence: 99%
“…It identifies an internal fault when the difference between the two circuits currents exceeds a certain threshold [10]- [12]. This technique is immune to the mutual coupling effect and provides faster operation speed compared to the distance algorithm.…”
Section: Introductionmentioning
confidence: 98%
“…Transverse differential protection scheme based on average current is proposed in Gilany et al (1995). This method has limitation for far end fault.…”
Section: Introductionmentioning
confidence: 99%